Results of an adult literacy program: reading, writing and numeracy assessment of a group of women in a rural environment - Junyent, Andrea Anahí; Fernández-Flecha, María de los Ángeles (Educação, 2025)
This work outlines the development and administration of an assessment instrument designed to evaluate reading, writing and numeracy skills. The instrument was specifically tailored to assess the performance of users of the Dispurse Literacy Programme —an adult literacy initiative conducted in Spanish within the rural Andes region in Peru—, which is designed taking into consideration the learners’ communicative and sociocultural context. The participants’ literacy skills were assessed primarily based on the programme’s goals. Their abilities were evaluated in accordance with the definitions of reading, writing, using numbers and performing basic operations provided by the Peruvian Educational System. Administered to a group of 49 women who had recently completed the programme, the instrument was crafted based on the sociocultural environment of the target demographic, employing items that simulate situations from the participants´ daily lives. The results of the assessment showed that participants had acquired fundamental competencies, with over 80% of them correctly answering most explicit and implicit questions on written texts, 90% capable of writing at least a short text; and the whole group showing a mean overall performance on numeracy items of 87.8%. The interpretation of the complete outcome of the administration provided insights on the resourcefulness with which participants are able to employ their acquired knowledge. Sharing this assessment tool and its development may be potentially useful for researchers engaged in similar studies, particularly those aiming to evaluate the outcomes of literacy programmes tailored to specific populations.